Teachers’ Impoliteness Strategies in Providing Feedback in a Microteaching Class - Rita Erlinda (Langkawi: Journal of The Association for Arabic and English, 2022)
The study discusses the impoliteness strategies used by the lecturers when giving feedback to the student-teachers in Microteaching classes. This study adopted a qualitative approach with a documentary analysis design. Data were gathered through recorded classroom interaction from eight microteaching classes when the lecturers gave comments and feedback to the student-teachers. Data were analyzed by using the theory of linguistic impoliteness strategies proposed by Culpeper (2005, 2011). This study's findings show that the lecturers employed positive, negative, and off-record impoliteness strategies when they give comments and feedback on student-teachers’ teaching performances. The significant findings of this study show three types of impoliteness strategies employed by the lecturers. Firstly, a positive impoliteness strategy was manifested in three strategies: using inappropriate identity markers, seeking disagreement, and using a derogatory name to call the hearer’s name. Secondly, the negative impoliteness strategy was realized in three strategies, such as frightening-instill a belief that action detrimental to others will occur, condescending, scorn, or ridicule in three forms, by emphasizing power, using diminutive to hearer's position, and by belittling, and explicitly associating hearer with negative aspects. Lastly, off-record politeness was found in two different strategies: criticizing-dispraise hearer and hindering-deny turn. This study demonstrates that the lecturers need to consider their utterances in giving comments and feedback to student-teacher because they can impact unpleasant feelings on the lecturers personally and demotivate the students to gain teaching skills better.